Electronic structure, photovoltage, and photocatalytic hydrogen evolution with p-CuBi2O4 nanocrystals. Issue 8 (15th January 2016) - Sharma, Geetu; Zhao, Zeqiong; Sarker, Pranab; Nail, Benjamin A.; Wang, Jiarui; Huda, Muhammad N.; Osterloh, Frank E.
Abstract : As a visible light active p-type semiconductor, CuBi2 O4 is of interest as a photocatalyst for the generation of hydrogen fuel from water. Abstract : As a visible light active p-type semiconductor, CuBi2 O4 is of interest as a photocatalyst for the generation of hydrogen fuel from water. Here we present the first photovoltage and photocatalytic measurements on this material and DFT results on its band structure. Single crystalline CuBi2 O4 nanoparticles (25.7 ± 4.7 nm) were synthesized from bismuth and cupric nitrate in water under hydrothermal conditions. Powder X-ray diffraction (XRD) confirms the CuBi2 O4 structure type and UV-Vis spectroscopy shows a 1.75 eV optical band gap. Surface photovoltage (SPV) measurements on CuBi2 O4 nanoparticle films on fluorine doped tin oxide yield 0.225 V positive photovoltage at >1.75 eV photon energy confirming holes as majority carriers. The photovoltage is reversible and limited by light absorption. When dispersed in 0.075 M aqueous potassium iodide solution, the CuBi2 O4 particles support photochemical hydrogen evolution of up to 16 μmol h −1 under ultraviolet but not under visible light. Based on electrochemical scans, CuBi2 O4 is unstable toward reduction at −0.2 V, but a pH-dependent photocurrent of 6.45 μA cm −2 with an onset potential of +0.75 V vs. NHE can be obtained with 0.01 M Na2 S2 O8 as a sacrificial electron acceptor. The photoelectrochemical properties of CuBi2 O4 can be explained on the basis of the band structure of the material. DFT calculations show that the valence and conduction band edges arise primarily from the combination of O 2p and Cu 3d orbitals, respectively, with additional contributions from Cu 3d and Bi 6s orbitals just below the Fermi level. Trapping of photoelectrons in the Cu 3d band is the cause for reductive photocorrosion of the material, while the p-type conductivity arises from copper vacancy states near the VB edge. These findings provide an improved understanding of the photophysical properties of p-CuBi2 O4 and its limitations as a proton reduction photocatalyst.